Islamic Spiritual Guidance on Changes In Blood Sugar Levels In Type 2 Diabetes Mellitus Patients - Al Fariqi, M Zulfikar (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2023)
Diabetes Mellitus in Indonesia is increasing every year. Diabetes mellitus can be prevented, delayed and slowed down by controlling blood glucose levels. Controlling blood glucose levels in diabetics can be done with Islamic spiritual guidance. This study aims to analyze the effect of Islamic spiritual guidance on changes in blood sugar levels in Type 2 Diabetes Mellitus patients. The research method used was quasi-experimental using a pretest-posttest two group design. A sample of 22 respondents for the intervention group and 22 respondents for the control group. Data analysis used Wilcoxon test, dependent t-test, and Spearman rank correlation. The results showed that the mean blood sugar levels of the intervention group decreased 17.96 mg / dl. Statistically there is influence of Islamic spiritual guidance on blood sugar level (p = 0,000). The total energy requirement is a confounding variable that affects changes in blood sugar levels (p = 0.002). Diabetes mellitus patients are expected to apply spiritual guidance of Islam regularly to control blood sugar levels in order to improve the health of the body and prevent complications of diabetes.